A prayer for Owen Meany [compact disc, unabridged] : a novel - Irving, John, 1942- (Brilliance Audio, 2009)
In the summer of 1953, two 11-year-old boys--best friends--are playing in a Little League baseball game in New Hampshire. One of the boys hits a foul ball that kills his best friend's mother. Owen Meany believes he didn't hit the ball by accident. He believes he is God's instrument. What happens to Owen after 1953 is extraordinary and terrifying. He is Irving's most heartbreaking hero.